Migration, Identity, and Voting Behavior in Border Regions of India (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This article discusses the impact of migration on political identity and voting behaviour in the border regions of India. Instead of seeing migration as just a demographic and/or economic phenomenon, the paper approaches it as a politically mediated phenomenon, and explores how its impacts rely upon historical memory, identity divisions, institutional rules, and party competition. The study takes a comparative qualitative approach using a structured, focused comparison of four cases: Assam, West Bengal, Punjab and Jammu & Kashmir, which were chosen to reflect variations across the cases in terms of the migration experience, the configuration of the borders, institutional response, and electoral mobilisation. The analysis is based on secondary sources such as the Census of India, government reports, institutional documents relating to elections and scholarly works on migration, ethnicity, citizenship, and voting behaviour. The paper suggests that migration is electorally salient because of demographic change framed within a security, religious, ethnic or linguistic lens, and when political actors transform such perceptions into organised narratives of inclusion or exclusion. In all the cases, five mechanisms are obtained: perceived threat, identity reconstitution, institutional regulation, clientelist incorporation, and spatial concentration. The article ends by suggesting that the politics of migration are not the same in all parts of India's borders, but will take different forms depending on the local histories, state power, party systems and citizenship laws. These findings have relevance for democratic inclusion, conflict-sensitive border governance, and designing fair documentation processes and enfranchisement.